EXPLORING THE UNIVERSE: THE EVER-EVOLVING LANDSCAPE OF PHYSICS - Ajaz Rashid Dar; Gul Mohammad Dar (PT. Radja Intercontinental Publishing, 2024)
This paper explores the multifaceted world of physics, a fundamental science dedicated to understanding the principles governing matter, energy, and their interactions. Key areas discussed include classical mechanics, electromagnetism, thermodynamics, quantum mechanics, and relativity, each foundational to modern scientific thought and technological progress. The historical milestones of physics are traced, from the scientific revolution and Newtonian mechanics to the electromagnetic and quantum revolutions, culminating in Einstein's theory of relativity. Modern advancements in particle physics, cosmology, condensed matter physics, and quantum computing are highlighted, showcasing groundbreaking discoveries like the Higgs boson and gravitational waves. The paper also delves into future directions in physics, including unification theories, the study of dark matter and dark energy, advancements in gravitational wave astronomy, and the potential of quantum technologies. As physics continues to evolve, it not only deepens our understanding of the universe but also propels innovation across various scientific and industrial domains.